Integrating hepatitis B care and treatment with existing HIV services is possible: cost of integrated HIV and hepatitis B treatment in a low-resource setting: a cross-sectional hospital-based cost-minimisation assessment - Andrew Kambugu; Philippa Easterbrook; Jacinto Amandua; David Livingstone Ejalu; Joan N Mutyoba; Claude Wandera; Emmanuel Seremba; Alex Muganzi; Racheal Beyagira; Kaggwa Mugagga; Ponsiano Ocama (BMJ Open)
Background Hepatitis B and HIV care share health system challenges in the implementation of primary prevention, screening, early linkage to care, monitoring of therapeutic success and long-term medication adherence.Setting Arua regional referral hospital (RRH) and Koboko district hospital (DH), the West Nile region of Uganda.Design A cross-sectional hospital-based cost minimisation study from the providers’ perspective considers financial costs to measure the amount of money spent on resources used in the stand-alone and integrated pathways.Data sources Clinic inputs and procurement invoices, budgetary documents, open market information and expert opinion. Data were extracted from 3121 files of HIV and hepatitis B virus (HBV) monoinfected patients from the two study sites.Objective To estimate provider costs associated with running an integrated HBV and HIV clinical pathway for patients on lifelong treatment in low-resource setting in Uganda.Outcome measures The annual cost per patient was simulated based on the total amount of resources spent for all the expected number of patient visits to the facility for HBV or HIV care per year.Results Findings showed that Arua hospital had a higher cost per patient in both clinics than did Koboko Hospital. The cost per HBV patient was US$163.59 in Arua and US$145.76 in Koboko while the cost per HIV patient was US$176.52 in Arua and US$173.23 in Koboko. The integration resulted in a total saving of US$36.73 per patient per year in Arua RRH and US$17.5 in Koboko DH.Conclusion The application of the integrated Pathway in HIV and HBV patient management could improve hospital cost efficiency compared with operating stand-alone clinics.